Emerging Cases of Professional Misconduct of Legal Practitioners in Nigeria: A Case for Law Reform - Ehirim, Ugochukwu Godspower; Oyibodoro, Ufuoma Garvin; Ehirim , Nwanneka Flora (Universitas Muhammadiyah Malang, 2024)
In recent times, the Bar, the Bench, and the general public have been alarmed by the increasing and expansive dimension of misconduct of legal practitioners in Nigeria. This paper takes a critical look at the emerging cases of professional misconduct among lawyers in Nigeria. It sets out with an introductory part that gives an overview of what is considered professional misconduct by a lawyer in Nigeria. The main body of the paper dwells on the statutory regulation of the legal profession with a focus on ethics in legal practice. Some recent cases of professional misconduct of legal practitioners are reviewed leading to the interrogation of the rationale for establishing a case of professional misconduct of a lawyer in Nigeria pointing to the need for a more pragmatic approach. The paper concludes with the position that while the need for a lawyer to remain a light bearer, a leader worthy in learning and character because of the nobility of his calling is inviolate, the thin line between a lawyer’s professional and private life should be identified and respected to contain the expansive cases of misconduct. The point is made that the law which holds every act of a legal practitioner to a standard even where such an act was not done in a professional capacity deserves reformation. Recommendations are proffered to suggest ways of reducing cases of misconduct of lawyers without lowering the standards at the Bar.